An unsymmetrical phosphonium diylide with a fluorenylidene subunit and its lithium complexes - Geitner, Robert; Kosygin, Irina; Görls, Helmar; Pahl, Jürgen; Harder, Sjoerd; Westerhausen, Matthias; Langer, Jens (Journal of Coordination Chemistry, 2015)
The phosphonium ylide MePh2P(flu) (3) (flu = C13H8, fluorenylidene) was conveniently prepared by reaction of Ph2P(fluH) (1) (fluH = C13H9, fluorenyl) with iodomethane, followed by subsequent dehydrohalogenation of the resulting phosphonium salt [MePh2P(fluH)] I (2) by potassium tert-butoxide. Compound 3 was further deprotonated by n-butyllithium, yielding the corresponding lithium complex [LiCH2PPh2(flu)(tmeda)] (4) in presence of N,N,N',N'-tetramethylethylenediamine (tmeda). This mononuclear lithium compound contains the monoanionic chelating diylidic ligand. An exchange of the neutral bidentate tmeda by tridentate N,N,N',N'',N''-pentamethyldiethylenetriamine (pmdta) enforces a change in coordination mode. Consequently, the diylide is monodentate in [LiCH2PPh2(flu)(pmdta)] (5). Compounds 1-5 were characterized by NMR spectroscopy and single-crystal X-ray diffraction experiments.
Keywords: Lithium; Phosphonium halides; Phosphonium ylides; Diylides; Phosphanes; Fluorenylidene; X-ray crystallography